Microcirculatory alterations are associated with pulmonary dead-space fraction in moderate and severe ards (2015)
Shunt-induced hypoxemia i s considered the primary pathophysiological abnormality and main diagnostic cri- teria of acute respiratory distress syndrome (ARDS). However, increases in dead- space ventilation (VD/VT) can also contribute to gas exchange alterations in ARDS. Systemic microcirculatory alterations described during inflammatory conditions are characterized by perfusion heterogeneity and theoretically pulmonary microcirculatory heterogene ity could lead to imbalance pulmonary ventilation/perfusion relationship. Thus, we hypothesized that systemic microvascular alterations could reflect increased VD/VT in ARDS.